Sub-micron pit-formation using ultrashort pulsed laser - Tan, Bo (2008)
The objective of this research work is to increase the data recording density of optical disk by reducing the information element size, on selected recording medium, by using ultrashort pulsed laser ablation. These miniaturised pits place higher demands on the positioning of the information element..